Messages - Suchatvee Suwansawat (My University, 2021)
This conference was organized by KMITL subdivisions that are College of Nanotechnology, School of Engineering and KMITL-Chaokhunthahan Hospital Foundation incorporated with IEEE Thailand Section.It will serve as an opportunity for Thai and oversea researchers, lecturers, young scientists and students as well as those who are interested in Engineering, Applied Sciences and Technology to discuss and exchange their scientific progress and also to develop and strengthen the collaboration network among the research community.
Keywords: null